2018
DOI: 10.5114/aoms.2017.71855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of heterozygous familial hypercholesterolemia in a Polish outpatient metabolic clinic: a retrospective observational study

Abstract: IntroductionThere are currently no reports available from a Polish clinical practice on heterozygous familial hypercholesterolemia (HeFH) management. The aim of this study was to test the efficacy of HeFH hypolipidemic treatment in a Polish outpatient metabolic clinic according to treatment targets outlined in the European Atherosclerosis Society (EAS) and European Society of Cardiology (ESC) guidelines.Material and methodsThis retrospective, observational study was performed on HeFH patients who attended thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Of 3625 citations of observational studies, we included four cohort retrospective cohorts with 1667 participants in our narrative summary (figure 2, table 2, and online supplemental table S10). [31][32][33][34] Follow-up durations ranged from 72 to 400 weeks (that is, 1.38-7.70 years; median 282 weeks (that is, 5.42 years)). The population from two studies were identified from electronic health records.…”
Section: Results Included Studiesmentioning
confidence: 99%
“…Of 3625 citations of observational studies, we included four cohort retrospective cohorts with 1667 participants in our narrative summary (figure 2, table 2, and online supplemental table S10). [31][32][33][34] Follow-up durations ranged from 72 to 400 weeks (that is, 1.38-7.70 years; median 282 weeks (that is, 5.42 years)). The population from two studies were identified from electronic health records.…”
Section: Results Included Studiesmentioning
confidence: 99%
“…Another study in Dutch patients with genetically or clinically diagnosed heterozygous FH (n 5 1249; 96% on statins) observed that 21% of patients reached a goal of ,2.6 mmol/L, and 46% of those with LDL-C .2.6 mmol/L achieved a .50% reduction in LDL-C. 7 Recently, a study of 222 patients from Poland with definite or probable FH (according to DLCN criteria) reported that 25.2% of patients achieved an LDL-C goal of ,1.8 mmol/ L or ,2.6 mmol/L, for those at very high or high CV risk, respectively, and 55.9% of patients achieved an LDL-C reduction of at least 50%. 13 Only 43.1% of patients with definite or probable FH had genetically confirmed FH. It was not possible to distinguish whether patients without genetic confirmation were not tested, or were tested but no mutation was identified.…”
Section: Discussionmentioning
confidence: 99%